2019
DOI: 10.1111/aos.14215
|View full text |Cite
|
Sign up to set email alerts
|

Suction stability management in small incision lenticule extraction: incidence and outcomes of suction loss in 4000 consecutive procedures

Abstract: Purpose: To report the incidence and outcomes of suction loss during small incision lenticule extraction (SMILE). Methods: The incidence of suction loss was measured over 4000 consecutive SMILE procedures and categorized by cause, the interface in which suction was lost and management (restart/continue SMILE, re-SMILE thinner cap, convert to laser in-situ keratomileusis [LASIK]). One-year outcomes were compared to the fellow eye where no suction loss occurred. Results: There were 20 cases of suction loss (0.50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
0
23
0
3
Order By: Relevance
“…In our study, suction loss in 19 (61.3%) eyes occurred during the cap interface stage and 8 (25.8%) during the creation of small incision. The respective numbers were 45% and 15% as reported by Reinstein [7] and 51% and 3% as reported by Liu [13]. One possible explanation for this phenomenon is that the air bubbles generated from lenticule cutting obscure the patient's vision.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In our study, suction loss in 19 (61.3%) eyes occurred during the cap interface stage and 8 (25.8%) during the creation of small incision. The respective numbers were 45% and 15% as reported by Reinstein [7] and 51% and 3% as reported by Liu [13]. One possible explanation for this phenomenon is that the air bubbles generated from lenticule cutting obscure the patient's vision.…”
Section: Discussionmentioning
confidence: 59%
“…A review by Reinstein reported that the average global incidence of suction loss during SMILE surgery is 0.72% [7]. In studies involving large population of more than 1000 cases, the reported incidence of suction loss ranges from 0.17-2.10% [4,7,9,11,[13][14][15]. As doctors become more experienced, the incidence of suction loss decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wenn den empfohlenen Maßnahmen gefolgt wird, sind die visuellen Ergebnisse nach einem Vakuumverlust nicht beeinträchtigt [28].…”
Section: Intraoperative Komplikationenunclassified
“…However, intraoperative and postoperative complications can still be observed [3][4][5][6][7]. The possible complications of SMILE surgery include suction loss, di culty or inability to extract the lenticule, and abrasion or minor tears in the small incision [8,9].…”
Section: Introductionmentioning
confidence: 99%